2012
DOI: 10.1093/jac/dks319
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acquired fosfomycin resistance among extended-spectrum  -lactamase-producing Escherichia coli and Klebsiella pneumoniae clinical isolates in Korea and IS26-composite transposon surrounding fosA3

Abstract: An IS26-composite transposon appears to be the main vehicle for dissemination of fosA3 in E. coli and K. pneumoniae of diverse clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
90
5
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 20 publications
15
90
5
3
Order By: Relevance
“…However, because the number of the isolates used in the present study was limited, further evaluation will be required to determine whether our test can be used to identify all types of FR-GST producers. Recently, it was reported that the fosA3 gene has been detected in Klebsiella pneumoniae clinical isolates (7). Future studies are required to evaluate the capability of the test developed here to detect FR-GST producers other than E. coli.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, because the number of the isolates used in the present study was limited, further evaluation will be required to determine whether our test can be used to identify all types of FR-GST producers. Recently, it was reported that the fosA3 gene has been detected in Klebsiella pneumoniae clinical isolates (7). Future studies are required to evaluate the capability of the test developed here to detect FR-GST producers other than E. coli.…”
Section: Discussionmentioning
confidence: 97%
“…Since our first report of fosfomycin-resistant E. coli organisms producing FosA3 in 2010, reports from East Asian countries have identified many FosA3 producers in E. coli isolates from clinical specimens (7), healthy individuals (6), consumable animal products (8,9), and domestic animals (10). Further spread of the gene encoding FosA3 would be a serious public health concern because of the global distribution of CTX-M-type ESBL producers in a variety of settings (11).…”
mentioning
confidence: 99%
“…New subtypes, with similar structure, of the gene have been described (fosA2, fosA3, fosA4, and fosA5) (108)(109)(110). Cooccurrence in plasmids with bla CTX-M , bla NDM , bla KPC , bla OXA , bla CMY , bla AmpC , bla TEM , bla SHV , bla SFO-1 , gyrA, parC, parE, sul1, sul2, strA, strB, aac(6=)-Ib, aadA5, aphA6, tetA(A), mphA, floR, dfrA7, rmtB, and merA genes has been reported, conferring resistance to ␤-lactams, quinolones, aminoglycosides, macrolides, sulfonamides, and tetracyclines (75,80,(111)(112)(113)(114). The genes conferring resistance to fosfomycin could be transferred together with genes conferring resistance to other antibiotics in either the same or a conjugate plasmid (114).…”
Section: Acquired Resistancementioning
confidence: 99%
“…With respect of ESBL control, Cho et al [18] tested 277 isolates of ESBL-positive E. coli and Klebsiella pneumoniae from urine samples of patients with UTI, and showed that 243 out of the 277 (87.7%) isolates were susceptible to fosfomycin. In another study, a total of 347 non-duplicate ESBL-producing E. coli (165 isolates) and K. pneumoniae (182 isolates) were collected, and the susceptibility to fosfomycin was reported to be 92.9% in E. coli and 95.2% in K. pneumoniae (Table 2) [19].…”
Section: Discussionmentioning
confidence: 99%